2013
DOI: 10.1007/s11066-013-9079-3
|View full text |Cite
|
Sign up to set email alerts
|

Can social microblogging be used to forecast intraday exchange rates?

Abstract: The Efficient Market Hypothesis (EMH) is widely accepted to hold true under certain assumptions. One of its implications is that the prediction of stock prices at least in the short run cannot outperform the random walk model. Yet, recently many studies stressing the psychological and social dimension of financial behavior have challenged the validity of the EMH. Towards this aim, over the last few years, internet-based communication platforms and search engines have been used to extract early indicators of so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
2
13
0
Order By: Relevance
“…In the same vein of short term effects, P. Papaioannou, Russo, Papaioannou, and Siettos (2013) use Twitter information to model and predict high frequency daily fluctuations of the EUR/USD exchange rate. They notice, first, that more and more studies challenge the efficient market hypothesis and suggest including information gathered from social media into time series models to forecast exchange rates.…”
Section: Using Social Media To Forecast Stock Pricesmentioning
confidence: 99%
“…In the same vein of short term effects, P. Papaioannou, Russo, Papaioannou, and Siettos (2013) use Twitter information to model and predict high frequency daily fluctuations of the EUR/USD exchange rate. They notice, first, that more and more studies challenge the efficient market hypothesis and suggest including information gathered from social media into time series models to forecast exchange rates.…”
Section: Using Social Media To Forecast Stock Pricesmentioning
confidence: 99%
“…Papaioannou, Russo, Papaioannou, and Siettos (2013) analyze 20,250 tweets related to the EUR/USD exchange rate over the period (2010)(2011) to extract information about the types of orders that each Twitter user had made, and the target-price of each of these orders. The findings provide supportive evidence of the role of this information in predicting the very short (intra-daily) foreign exchange rate.…”
Section: Twitter Sentiment/information and Exchange Ratesmentioning
confidence: 99%
“…Papaioannou et al [5] reported that the information gleaned from microblogging platforms such as Twitter can enhance the forecasting efficiency of Intraday exchange rates. The analysis has shown that efficient market hypothesis supports the analysis of public discussions on Twitter, and vice versa.…”
Section: Efficient Market Hypothesismentioning
confidence: 99%